Faktor-Faktor yang Berhubungan dengan Skrining Kanker Serviks IVA pada Wanita Usia Subur (WUS) di Puskesmas Medan Deli Tahun 2025 - Khairani, Fatya; Lubis, Rahayu (Innovative: Journal Of Social Science Research, 2025)
Cervical cancer is still a problem in Indonesia. The global prevalence of cervical cancer is 50 per 100.000 people, while in Indonesia it is 87 per 100.000, making it the second place after breast cancer with a CFR of 56%. The high mortality rate occurs due to late screening, so that almost 70% of cancer incidents are known at an advanced stage. VIA screening as a prevention can be implemented at health center by women of childbearing age (30-50 years) who are married. The target of VIA screening implementation in the national cancer plan is 70% of WUS have done VIA screening by 2027. Medan Deli Public Health Center has provided VIA screening services, but the implementation target has not been achieved. This study aims to determine the factors related to VIA cervical cancer screening among women at Medan Deli Public Health Center. This type of research is analytic research with a cross sectional approach. The sample consisted of 85 respondents, selected through purposive sampling with a questionnaire. Data analysis using chi square test. The results showed that knowledge (p<0,001), age of first sexual intercourse (p<0,001), access information (p<0,001), husband support (p<0,001), and health worker support (p<0,001) were related. While the variables of marriage history (p=0,661), family history (p=1.000), and distance (p=1.000) were not related. Factors related with VIA screening were knowledge, age of first sexual intercourse, access information, husband support, and health worker support. It is expected that public awareness of health improve by enhancing knowledge through adequate access to information and encouraging support from husband. Medan Deli Public Health Center can expand the target of health education and implement of Monday routine VIA check.